Globalización, crecimiento manufacturero y cambio en la localización industrial en México - Sobrino, Luis Jaime (El Colegio de México A.C., 2002)
Mexico's incorporation into the process of globalization has meant substantial changes in economic policy whose sometimes contradictory mechanisms have helped improve macroeconomic variables and revealed the enormous structural challenges yet to be resolved. Two of the latter include the changing nature of the patterns of territorial location of economic activities and greater inequality in income distribution. This paper seeks to analyze the principal characteristics of economic evolution and the manufacturing industry in the country during the period from 1982-2000 and to examine its consequences for the structure and dynamics of the manufacturing industry by sate. To this end, it has used the technique of change and participation analysis and its interrelationship with a matrix of territorial competitiveness. All monetary values are expressed in constant 1993 prices.